2012
DOI: 10.1103/physrevlett.109.137005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Magnetic Exchange in Ferromagnet-SuperconductorLa2/3Ca1/3MnO3/YBa2

Abstract: The existence of coherent magnetic correlations in the normal phase of cuprate high temperature superconductors has proven difficult to measure directly. Here we report on a study of ferromagnetic/superconductor bilayers of La 2/3 Ca 1/3 MnO3/YBa2Cu3O7 (LCMO/YBCO), with varying YBCO layer thicknesses. Using X-ray magnetic circular dichroism it is demonstrated that the ferromagnetic layer induces a Cu magnetic moment in the adjacent high temperature superconductor. For thin samples, this moment exists at all te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
3
7
3
Order By: Relevance
“…It is thus a general property of to cuprate/manganite heterostructures and interfaces. The charge transfer modifies the superconducting doping only within 1-4 CuO 2 layers at the interface while, as shown by our calculations, the magnetisation profile in the cuprate layer is perturbed over at least 10-15 atomic layers, in agreement with the estimates made by Giblin et al 35 for YBCO/LCMO. The reduction of the critical temperature in our cuprate/manganite multilayers (more than 10 K, see Supplementary Materials) cannot be explained by the modest change of doping occurring in the first interfacial CuO 2 layers.…”
Section: Discussionsupporting
confidence: 80%
“…It is thus a general property of to cuprate/manganite heterostructures and interfaces. The charge transfer modifies the superconducting doping only within 1-4 CuO 2 layers at the interface while, as shown by our calculations, the magnetisation profile in the cuprate layer is perturbed over at least 10-15 atomic layers, in agreement with the estimates made by Giblin et al 35 for YBCO/LCMO. The reduction of the critical temperature in our cuprate/manganite multilayers (more than 10 K, see Supplementary Materials) cannot be explained by the modest change of doping occurring in the first interfacial CuO 2 layers.…”
Section: Discussionsupporting
confidence: 80%
“…It was reported that at 100 K, there was no Cu magnetic moment for a 25 u.c. YBCO layer in the LCMO/YBCO system 9 , where T SC was 80 K which is slightly higher than in our system.…”
Section: Resultscontrasting
confidence: 67%
“…On the one hand, the suppression of Mn magnetic moments at the interface was studied by polarized neutron reflectivity (PNR) 5 . On the other hand, X-ray linear dichroism (XLD), X-ray absorption spectroscopy (XAS) and X-ray magnetic circular dichroism (XMCD) studies indicated that an orbital reconstruction of the Cu atoms associated with a charge transfer across the interface and an anti-parallel coupling between the YBCO-LCMO interface are basically responsible for the proximity effect 69 . All these phenomena had been explained in terms of the covalent bonding of Cu and Mn atoms via the oxygen atom, which also rely on the specific interface termination 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the induced ferromagnetic spin moments in the interfacial CuO 2 plane below the Curie temperature of LCMO layer have been previously reported 6 28 29 30 , our RSXS data suggests that they may have coupled ferromagnetically along c -axis throughout the YBCO layer as the diffraction peak width is limited by the layer thickness. This c -axis ferromagnetic spin coupling is established at 80 K, just above the ~70 K superconducting transition temperature of YBCO under study.…”
Section: Resultscontrasting
confidence: 47%